Frequency of re-exploration for bleeding in ON PUMP versus OFF PUMP coronary artery bypass grafting at Peshawar Institute of Cardiology - Rahman, Ubaid Ur; Gohar, Muhammad Ali; Haseeb, Muhammad Abdul; Nisar, Muhammad; Iqbal, Aamir; Nasir, Abdul (International Journal of Pathology, 2025)
Background: Postoperative bleeding is a significant complication of on-pump coronary artery bypass grafting (CABG), due to an increased risk of coagulopathy compared to off-pump techniques. Due to limited local data, this study aimed to compare re-exploration rates for bleeding between on-pump and off-pump CABG. Methods: This cross-sectional study was conducted in the Department of Cardiac Surgery at the Peshawar Institute of Cardiology, enrolling 160 patients (80 per group) via consecutive sampling. Adults aged 30–80 years undergoing elective CABG were included. Patients with bleeding disorders, recent anticoagulant use, valvular disease, emergency, or re-do surgeries were excluded. Postoperative bleeding within 24 hours was assessed via clinical evaluation and drain output; re-exploration was defined as return to the OR within 24 hours. Data were analyzed using t-tests and chi-square tests, with significance set at p < 0.05. Results: The mean patient age was 57.16 ± 8.95 years, and 80.00% were male. Both groups were statistically similar in baseline characteristics (p > 0.05). Prior MI was noted in 12.5% (CABG) and 11.25% (OPCAB) of patients. Mean ejection fraction was 52.35 ± 7.23 (CABG) vs. 53.19 ± 6.73 (OPCAB). Triple-vessel disease was most common. CABG patients received more grafts (median: 3.0) compared to OPCAB (median: 2.0; p < 0.001). Re-exploration for bleeding occurred in 3 patients, all in the CABG group. One death was reported postoperatively. Conclusion: Both CABG and OPCAB are effective in managing complex coronary disease with low short-term mortality. However, CABG is associated with a higher number of grafts and re-exploration rates, while off-pump coronary artery bypass (OPCAB) offers a less invasive alternative with fewer complications. OPCAB may be preferred in high-risk patients without compromising outcomes.